The music of the other : new challenges for ethnomusicology in a global age - Aubert, Laurent (Ashgate., 2007)
Laurent Aubert considers the impact of world musics on our values, our habits and our cultural practices. He not only looks at the nature of Western society as a 'global village' but also the impact of current Western demands on the future of world musics and their practitioners.